A glimpse of Japanese ideals : - Harada, Jiro (Kokusai bunka shinkokai, 1937)
This book introduce about characteristics of the Japanese which have influenced, certain ideals and characteristics of Japanese art, a survey of Japanese archaeology. Japanese architecture.